Transformation of Poland’s spatial-economic structure in the years 1998–2008. - Czyż, Teresa (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
The article consists of two parts. Part one offers a diagnostic description of the current spatial-economic structure of Poland in which regions are divided into core and peripheral ones. The division rests on a systemic measure of the level of economic development, viz. the income potential /population potential ratio. Part two is an analysis of changes in Poland’s spatial-economic structure over the years 1998–2008 where an attempt is made to determine how far those changes coincided with visions of the country’s spatial structure presented in planning conceptions.
Keywords: spatial-economic structure; core and peripheral regions; method of potential ratio; transformation of spatial structure; planning conceptions; Poland